“Out of the map”: mapping services and the access by individuals with disabilities living in social vulnerability condition, in Santos City/SP, Brazil (Brazilian Journal of Health Research, 2021)
Introduction:The text addresses the rights of mobility and assistance of people with disabilities, in Santos city, SP. Objectives: The main aim of the present research is to address the supply and demand of services focusing on individuals with disabilities in order to widen, reflections about association among disability, social vulnerability and territory. Methods: Data were generated at three stages: the first stage comprised documentary survey about health services and social assistance provided to individuals with disabilities in Santos City-SP; the second stage referred to, six interviews conducted with individuals with disabilities, who lived in different regions in the city; and the third stage comprised services and the interviewees’ location on the city map. Results: Results were distributed on the map to enable the spatial visualization of services focusing on individuals with disabilities, as well as to check their concentration in Downtown and Urban Fringe regions. The comparison between the service and social vulnerability maps of the City enabled identifying the distance and low supply of services in zones of greater social vulnerability. The analysis applied to the interviews has pointed towards conflicts, difficulties and withdrawals from service usings, mainly among interviewees who lived in zones of greater social vulnerability. Conclusion: Cross-analysis of data provided by different sources enabled identifying a vulnerability expansion process. State plays the main role in this process, since social assistance, health and city-use rights are denied to these individuals on a daily basis; access and territorialization policies are often ignored. The study also addressed the need of expanding the supply of territorial services to individuals with disabilities, as well as of assuring their access to, and use of, other regions in the city.
Keywords: Individuals with disabilities; Residence features; Social vulnerability; Community-Institution Relationships